Involvement of the Cuneate Nucleus in the Acupuncture Inhibition of Drug-Seeking Behaviors - Chang, Suchan; Ryu, Yeonhee; Fan, Yu; Bang, Se Kyun; Kim, Nam Jun; Lee, Jin Gyeom; Kim, Jin Mook; Lee, Bong Hyo; Yang, Chae Ha; Kim, Hee Young (Frontiers in Neuroscience, 2019)
Our previous studies have shown that acupuncture suppresses addictive behaviors induced by drugs of abuse, including cocaine, morphine and ethanol, by modulating GABA neurons in the ventral tegmental area and dopamine release in the nucleus accumbens. The mechanisms by which the peripheral signals generated by acupoint stimulation are transmitted to brain reward systems are largely unexplored. The present study aims to investigate the role of spinal dorsal column somatosensory pathways in the acupuncture inhibition of drug addictive behaviors. Thus, we tested whether acupuncture at Shenmen (HT7) points reduces drug-seeking behaviors in rats self-administering morphine or ethanol and whether such effects are inhibited by the disruption of the cuneate nucleus (CN). The stimulation of HT7 suppressed morphine and ethanol self-administration, which were completely abolished by surgical lesioning of the CN. In in vivo extracellular recordings, single-unit activity of the CN was evoked during acupuncture stimulation. The results suggest that acupuncture suppresses morphine- and ethanol-seeking behaviors through the modulation of the CN, second-order neurons of the dorsal column somatosensory pathway.